Prevalence and determinants of cervical cancer screening in five sub-Saharan African countries: A population-based study. (June 2021) - Ba, Djibril M.; Ssentongo, Paddy; Musa, Jonah; Agbese, Edeanya; Diakite, Brehima; Traore, Cheick Bougadari; Wang, Steve; Maiga, Mamoudou
Highlights: Prevalence and determinants of cervical cancer screening in SSA was examined. The prevalence of cervical cancer screening is substantially low in SSA countries. There is a high degree of between-country variation in cervical cancer screening. Older age and having health insurance are some of the leading factors associated with screening. Abstract: Background: Cervical cancer is the fourth most common cancer among women worldwide, with an estimate of 570, 000 new cases and about 311, 000 deaths annually. Low-resource countries, including those in sub-Saharan Africa, have the highest-burden with an estimate of 84 % of all cervical cancers. This study examines the prevalence and socio-demographic-economic factors associated with cervical cancer screening in sub-Saharan Africa. Methods: A weighted population-based cross-sectional study using Demographic and Health Surveys data. We used available data on cervical cancer screening between 2011 and 2018 from the Demographic and Health Surveys for five sub-Saharan African countries (Benin, Ivory Coast, Kenya, Namibia, and Zimbabwe). The study population included women of childbearing age, 21–49 years (n = 28, 976). We fit a multivariable Poisson regression model to identify independent factors associated with cervical cancer screening. Results: The overall weighted prevalence of cervical cancer screening was 19.0 % (95 % CI: 18.5 %–19.5 %) ranging from 0.7 % in Benin to 45.9 % in Namibia. Independent determinants of cervical cancer screening were: older age (40−49 years) adjusted prevalence ratio (aPR) = 1.77 (95 % CI: 1.64, 1.90) compared with younger age (21−29 years), secondary/higher education (aPR = 1.51, 95 CI: 1.28–1.79) compared with no education, health insurance (aPR = 1.53, 95 % CI: 1.44–1.61) compared with no insurance, and highest socioeconomic status (aPR = 1.39, 95 % CI: 1.26–1.52) compared with lowest. Conclusion: The prevalence of cervical cancer screening is substantially low in sub-Saharan Africa countries and shows a high degree of between-country variation. Interventions aimed at increasing the uptake of cervical cancer screening in sub-Saharan Africa are critically needed.